2020
DOI: 10.1039/d0cc06552h
|View full text |Cite
|
Sign up to set email alerts
|

Organic single crystals of cyano-substituted p-phenylene vinylene derivatives as transistors with low surface trap density

Abstract: We report the preparation of two high-quality lamellar crystals of cayno-substituted p-phenylene vinylene derivatives and the fabrication of their transistors. The transistors were demonstrated hysteresis-free, low subthreshold swing of 0.10...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Organic single crystals with cofacial stacking are much less reported. Among crystals with cofacial arrangements, the hole mobilities of 3,7‐bis(( E )‐1‐(2‐ethylhexyl)‐5,7‐difluoro‐2‐oxoindolin‐3‐ylidene)‐3,7‐dihydrobenzo[1,2‐b:4,5‐b′]difuran‐2,6‐dione (F 4 ‐BDOPV) [42] and (2Z,2′Z)‐2,2′‐(1,4‐phenylene)bis(3‐(thiophen‐3‐yl)acrylonitrile) (α‐PBTA) [43] reached 12.6 and 2.7 cm 2 V −1 s −1 , respectively (Table S4). Compared with the above crystal packing modes and their benchmark carrier mobilities, our system compares favorably with previously reported cofacial single crystals.…”
Section: Resultsmentioning
confidence: 99%
“…Organic single crystals with cofacial stacking are much less reported. Among crystals with cofacial arrangements, the hole mobilities of 3,7‐bis(( E )‐1‐(2‐ethylhexyl)‐5,7‐difluoro‐2‐oxoindolin‐3‐ylidene)‐3,7‐dihydrobenzo[1,2‐b:4,5‐b′]difuran‐2,6‐dione (F 4 ‐BDOPV) [42] and (2Z,2′Z)‐2,2′‐(1,4‐phenylene)bis(3‐(thiophen‐3‐yl)acrylonitrile) (α‐PBTA) [43] reached 12.6 and 2.7 cm 2 V −1 s −1 , respectively (Table S4). Compared with the above crystal packing modes and their benchmark carrier mobilities, our system compares favorably with previously reported cofacial single crystals.…”
Section: Resultsmentioning
confidence: 99%
“…The authors systematically investigated the defect density of NBTA single crystals, and the number of defects in NBTA single crystals was calculated as 1/9.22 × 10 3 . [ 103 ] The authors concluded that the stronger the intermolecular interaction forces, the lower the number of intrinsic defects produced and, thus, the better the device performance. Subsequently, the Ca and Au electrodes were evaporated on each end of the crystal using a stepwise method.…”
Section: Advances On Ossclet Devicesmentioning
confidence: 99%
“…Organic π-conjugated molecules have been actively studied in recent decades due to their advantages over inorganic materials, such as lightweight, flexibility, and low cost. Among them, distyrylbenzene (DSB in Figure a) and its derivatives have been reported to have many applications because of their easy synthesis and the possibility of introducing many functional groups. Distyrylbenzene, which can be regarded as an oligomer model of poly­( para -phenylenevinylene), has been studied to understand the correlation between its molecular structure and physical properties . Many reports have been published on distyrylbenzene derivatives with electron-withdrawing groups such as cyano, trifluoromethyl, and trifluoro­methane­sulfonyl groups at the vinyl position in the fields of fluorescence molecules, organic field effect transistors, and bioimaging (Figure b). Although many studies have been conducted on distyrylbenzene derivatives with various substituents at the vinyl position including a difluorovinylene derivative due to their unique properties, there are no reports on physical properties and functionalities of distyrylbenzene derivatives with a single fluorine substituent, a sterically small electron-withdrawing group, at the vinyl position.…”
mentioning
confidence: 99%